2008
DOI: 10.1186/1471-230x-8-40
|View full text |Cite
|
Sign up to set email alerts
|

Resveratrol inhibits nonalcoholic fatty liver disease in rats

Abstract: Background: The prevalence of nonalcoholic fatty liver disease (NAFLD) is high. NAFLD is linked to obesity, diabetes mellitus, and hypertriglyceridemia. Approximately 20% of patients with NAFLD will eventually develop cirrhosis. Our purpose was to investigate whether resveratrol decreased hepatic steatosis in an animal model of steatosis, and whether this therapeutic approach resulted in a decrease in tumor necrosis factor (TNF-) production, lipid peroxidation and oxidative stress.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
128
1

Year Published

2010
2010
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 188 publications
(146 citation statements)
references
References 37 publications
16
128
1
Order By: Relevance
“…31,32 In fact, antioxidant supplements have been proposed to treat patients with NAFLD. 33,34 We also found increased hepatocellular apoptosis in obese rats exposed to CS. This mechanism of cell death has been recently implicated in the pathogenesis of NASH in humans.…”
Section: Discussionmentioning
confidence: 49%
“…31,32 In fact, antioxidant supplements have been proposed to treat patients with NAFLD. 33,34 We also found increased hepatocellular apoptosis in obese rats exposed to CS. This mechanism of cell death has been recently implicated in the pathogenesis of NASH in humans.…”
Section: Discussionmentioning
confidence: 49%
“…Among other effects, this compound decreases hepatic steatosis severity in rats (Bujanda et al, 2008) and exerts an inhibitory effect on insulin secretion (Szkudelski, 2007). Although antiobesity actions of resveratrol have been extensively described in isolated adipocytes and in mice, including increased lipolysis and reduced lipogenesis in mature adipocytes, decreased adipogenesis and viability in maturing preadipocytes or protection from HFD-induced weight gain in mice (Baile et al, 2011), for the moment there are no big intervention trials showing similar effects in humans.…”
Section: Polyphenols and Other Plant Compoundsmentioning
confidence: 99%
“…However, it is worthwhile to note that ALT is more commonly used for screening of liver problems, as the AST level may also be increased as a result of deficiencies or diseases in other bodyorgans. 31 Administering of Lead acetate to rats showed a significant increase of AST in the rat's serum compared with the control group. The high values of these enzymes came in agreement with the finding of Haque who reported that following lead acetate administration significant elevation of AST was observed.…”
Section: Discussionmentioning
confidence: 99%